Sulfonated graphene, modified positive electrode material and preparation method and application of sulfonated graphene and modified positive electrode material

By performing pre-reaction under a non-reacting medium and performing high-pressure hydrothermal reaction in an aqueous medium, sulfonated graphene with suitable sheet size was prepared, which solved the problem that sulfonated graphene in the prior art was unable to effectively improve the magnification and circulation performance of lithium-ion batteries, and achieved the effect of significantly improving the magnification and circulation performance of the battery.

CN119750562AActive Publication Date: 2025-04-04XIAMEN KNANO GRAPHENE TECH CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411970895.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

When the carbon-clad material of sulfonated graphene as the positive electrode material in the prior art, the rate performance and cycling performance of lithium-ion batteries cannot be significantly improved, mainly because the resulting sulfonated graphene sheet diameter is too large and it is impossible to effectively wrap the nano-scale positive electrode material.

Method used

Using the new sulfonated graphene preparation method, sulfonated graphene with suitable sheet size is obtained by pre-reacting organic materials and sulfonating agent under a non-reacting medium, and then conducting high-pressure hydrothermal reaction in an aqueous medium.

Benefits of technology

Significantly improve the rate performance and cycling performance of lithium-ion batteries, and by forming an effective conductive layer and improving the conductivity of the positive electrode material, ensuring that the battery maintains good conductivity during multiple cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750562A_ABST
    Figure CN119750562A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of graphene modification, and particularly relates to sulfonated graphene, a modified positive electrode material and a preparation method and application of the sulfonated graphene and the modified positive electrode material. The preparation method of the sulfonated graphene comprises the following steps: S1, carrying out pre-reaction on an organic material and a sulfonating agent at 30-35 DEG C in the absence of a reaction medium to obtain a pre-reaction product; and S2, dispersing the pre-reaction product in water, heating the obtained dispersion liquid to 160-220 DEG C, and carrying out a high-pressure hydrothermal reaction to obtain the sulfonated graphene. When the sulfonated graphene obtained by the method provided by the invention is used for coating a positive electrode material, the rate capability and the cycle performance of the lithium ion battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of graphene modification, and specifically relates to sulfonated graphene and modified positive electrode material, and preparation methods and applications thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable electrical devices such as mobile phones, digital cameras and laptops due to their high operating voltage, high specific energy, long life and no memory effect. At the same time, they have also been widely used in new energy vehicles and energy storage devices as a substitute for petroleum. For lithium-ion batteries, the cathode material not only accounts for the highest proportion of the battery cost, but its performance is also the main factor affecting the overall electrochemical performance and safety of the battery. Olivine-type lithium iron phosphate cathode materials have become one of the hot spots for research and development in various countries around the world due to their rich resources, long cycle life and good safety. They are widely used in new energy vehicles, energy storage equipment, uninterruptible power supplies, power tools and other fields, and have a very broad market prospect. Studies have found that smaller cathode material particle size can minimize mechanical stress and provide better battery cycle performance. When the particle size of lithium iron phosphate is reduced from micron to nanometer, the conductivity and diffusion coefficient of the cathode material will increase significantly, and can even increase by an order of magnitude, thereby significantly improving battery performance. Therefore, nanoscale cathode material particles will also become a trend in the development of the cathode material industry. However, the low conductivity of pure LiFePO4 cathode materials limits its rate and cycle performance. To address this problem, LiFePO4 positive electrode materials are currently usually modified by carbon coating. The carbon coating layer can improve the conductivity of the LiFePO4 positive electrode material and isolate the electrolyte, thereby improving the rate performance and cycle performance of the lithium-ion battery.

[0003] The materials for forming the carbon coating layer include graphene, glucose, sucrose, etc. Among them, glucose and sucrose are small organic molecules, and the positive electrode materials using them as the coating layer, a large amount of hydrocarbon components in glucose and sucrose escape in the form of gas during the heat treatment process, causing the residual carbon to be attached to the surface of the positive electrode material in a mesh or even discontinuous form, and at the same time, the structure of the residual carbon of glucose and sucrose organic matter in the heat treatment is poor, resulting in poor conductivity, which will eventually affect the electrochemical performance of the battery. Although conventional graphene materials have excellent electrical conductivity, they are easy to agglomerate and difficult to be evenly dispersed on the surface of the positive electrode material. Using them as carbon coating layer forming materials will make the resulting positive electrode material have strong oxidizing properties at the end of charging, resulting in a large amount of oxygen release, weakening the rate performance and cycle performance of the battery. In this regard, the prior art has adopted sulfonation modification of graphene to improve its water solubility, thereby enabling it to be more evenly dispersed in the positive electrode material. Regarding the preparation method of sulfonated graphene, CN105764839A discloses a method for preparing sulfonated graphene from an organic material, the method comprising reacting the organic material with an oxidizing sulfonating agent in a reaction medium at a first temperature, and then in the same reaction medium, raising the reaction temperature to a second temperature to allow it to continue to react, the first temperature being the melting temperature of the organic material to below the boiling point of the reaction medium, and the second temperature being above the boiling point of the reaction medium, thereby obtaining sulfonated graphene. However, the sulfonated graphene obtained by this method cannot significantly improve the rate performance and cycle performance of lithium-ion batteries when used as a carbon coating material for positive electrode materials. Summary of the invention

[0004] The first purpose of the present invention is to overcome the problem that the sulfonated graphene prepared by the existing method cannot improve the rate performance and cycle performance of the carbon coating material of the positive electrode material, and to provide a new method for preparing sulfonated graphene, so that the sulfonated graphene obtained can significantly improve the rate performance and cycle performance of lithium-ion batteries.

[0005] Specifically, the preparation method of sulfonated graphene provided by the present invention comprises the following steps:

[0006] S1. Pre-reacting the organic material and the sulfonating agent at 30 to 35° C. in the absence of a reaction medium to obtain a pre-reaction product;

[0007] S2. Dispersing the pre-reaction product in water, and then heating the resulting dispersion to 160-220° C. to perform a high-pressure hydrothermal reaction to obtain sulfonated graphene.

[0008] The second object of the present invention is to provide sulfonated graphene prepared by the above method.

[0009] The third object of the present invention is to provide the use of the sulfonated graphene as a carbon material coating agent for positive electrode materials.

[0010] The fourth object of the present invention is to provide a modified positive electrode material, which comprises a positive electrode material substrate and a coating layer coated on the surface of the positive electrode material substrate, wherein the coating layer is formed by the above-mentioned sulfonated graphene.

[0011] The fifth object of the present invention is to provide a method for preparing the above-mentioned modified positive electrode material, which comprises dispersing the above-mentioned sulfonated graphene in water, then uniformly mixing the obtained sulfonated graphene dispersion with the positive electrode material and / or the positive electrode material precursor, and then filtering, drying and calcining the obtained mixture in sequence to obtain the modified positive electrode material.

[0012] After in-depth and extensive research, the inventors of the present invention found that when the sulfonated graphene obtained by the method disclosed in CN105764839A is used to coat the positive electrode material, the reason why the rate performance and cycle performance of the lithium ion battery cannot be well improved is that: although the sulfonated graphene obtained by this method has good hydrophilicity, the sheet diameter is too large. When it is used as a carbon coating material for the positive electrode material, it will form a pomegranate-shaped package, and it is impossible to achieve a comprehensive and effective package of the nano-scale positive electrode material, which will result in the inability to form an effective conductive layer on the surface of the positive electrode material. At the same time, part of the positive electrode material is still exposed to the electrolyte, and it is inevitable that the rate performance and cycle performance of the lithium ion battery cannot be improved. In addition, the first temperature of CN105764839A generally needs to be carried out at a higher temperature, in order to oxidize the organic material into a carbon material such as graphene, and a small amount of carbon is sulfonated, and a larger-scale crystal nucleus is formed at the same time, so as to facilitate the formation of large-diameter graphene at a higher temperature of the second temperature.

[0013] The key of the present invention is to pre-react the organic material and the sulfonating agent at a relatively low temperature in the absence of a reaction medium, and then perform a high-pressure hydrothermal reaction at a relatively high temperature under the condition of water as a medium, so that the obtained sulfonated graphene can significantly improve the rate performance and cycle performance of the lithium-ion battery when coating the positive electrode material. The reason for this is speculated to be that: the sulfonic acid agent is usually a superacid, and it is contacted with the organic material in the absence of a reaction medium, so that it can be densely distributed around the organic material, and the organic material is dehydrogenated, condensed and carbonized at a relatively low temperature with the sulfonating agent as a catalytic medium and preliminarily decomposed into nano-scale carbon micro-sheets. At the same time, due to the low reaction temperature, the fusion of small-diameter carbon micro-sheets into large-diameter carbon micro-sheets can be effectively avoided; the pre-reaction product is dispersed in water, so that the further fusion growth reaction of the small-diameter carbon micro-sheets formed at a relatively low temperature is quenched, ensuring that the diameter of the sheet no longer expands. At the same time, the sulfonating agent contacts water to generate sulfuric acid and hydrochloric acid. In the subsequent high-pressure hydrothermal reaction process, the residual organic matter in the pre-reaction product is fully dehydrogenated, condensed and carbonized in the mixed acid solution medium to improve the product yield. The carbon microsheets formed at a lower temperature and the carbon microsheets formed by the dehydrogenation and condensation of the residual organic matter in the high-pressure hydrothermal reaction system will also undergo a transformation from an amorphous carbon structure to a carbon structure with a higher degree of crystallinity. In addition, the sulfonic acid groups of the sulfuric acid in the hydrothermal reaction system dissociated in the high-pressure hydrothermal reactor are suspended on the surface or edge of the carbon material, thereby forming a sulfonated graphene with good water solubility and few defects at a nanoscale, so that it not only has the conductivity of graphene but also has good water solubility, which is more conducive to improving the conductivity of the positive electrode material and giving the lithium-ion battery good rate performance. At the same time, since the obtained graphene structure has fewer defects, the conductivity can still be maintained at a high level after multiple cycles, giving the lithium-ion battery good cycle performance. Furthermore, the sulfonated graphene provided by the present invention has good water solubility and a nanometer particle size, which can effectively improve the conductivity of the positive electrode material, and the positive electrode material can be effectively coated without subsequent grinding and refining of the particle size. In addition, the raw materials for preparing the sulfonated graphene provided by the present invention are cheap and easy to obtain. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is a Raman spectrum of the sulfonated graphene powder obtained in Preparation Example 1;

[0015] Figure 2 is a scanning electron microscope (SEM) image of the sulfonated graphene powder obtained in Preparation Example 1;

[0016] Figure 3 is the infrared spectrum of the sulfonated graphene powder obtained in Preparation Example 1;

[0017] Figure 4 This is the Raman spectrum of the sulfonated graphene powder obtained in Comparative Preparation Example 2. DETAILED DESCRIPTION

[0018] It should be noted that, in the present invention, all numerical values, whether or not explicitly indicated, are defined herein as modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art considers to be equivalent to the stated value to produce substantially the same properties, functions, results, etc. A numerical range indicated by a low value and a high value is defined to include all numerical values ​​included in the numerical range and all sub-ranges included in the numerical range.

[0019] The preparation method of sulfonated graphene provided by the present invention comprises the following steps:

[0020] S1. Pre-reacting the organic material and the sulfonating agent in the absence of a reaction medium to obtain a pre-reaction product;

[0021] S2. Dispersing the pre-reaction product in water, and then subjecting the obtained dispersion to a high-pressure hydrothermal reaction to obtain sulfonated graphene.

[0022] In the present invention, the mass ratio of the organic material to the sulfonating agent is preferably 1:(10-20), specifically 1:10, 1:12, 1:14, 1:16, 1:18, 1:20 or any value therebetween. The ratio of the organic material to the sulfonating agent can be any point value within the above range, which is not enumerated here.

[0023] The present invention has no particular limitation on the type of organic material, and can be any existing material capable of carbonizing to generate graphene, can be a small molecule organic material, can be a polymer organic material, or can be a mixture of a small molecule organic material and a polymer organic material. Among them, the small molecule organic material can be listed as at least one of toluene, xylene, styrene, naphthalene, phenylacetylene, n-hexane, n-octane, etc. The macromolecular organic material can be listed as at least one of polyethylene, polypropylene, polystyrene, styrene-butadiene rubber, isoprene rubber, ethylene-propylene rubber, butadiene rubber, etc. The organic material is particularly preferably polypropylene. The inventors of the present invention have found that when polypropylene is selected as the organic material, the obtained sulfonated graphene is more conducive to the improvement of the rate performance and cycle performance of the lithium ion battery by coating and modifying the positive electrode material. The reason is speculated to be: the unique carbon chain structure of polypropylene, the alternating carbon atoms on the carbon chain carry a methyl group, and the presence of the methyl group makes the molecular chain of polypropylene have a certain rigidity and regularity. When reacting with the sulfonating agent, the reaction rate is moderate, which is more conducive to controllable nucleation growth and easier to obtain nanoscale small-diameter graphene, which can achieve better coating of the positive electrode material and is beneficial to improving the conductivity of the positive electrode material.

[0024] The number average molecular weight of the macromolecular organic material is preferably 5000 to 150000, specifically 5000, 8000, 10000, 20000, 40000, 60000, 80000, 100000, 120000, 140000, 150000 or any value therebetween. In addition, the small molecule organic material and the high molecular organic material may be substituted by heteroatoms or may not be substituted by heteroatoms. The heteroatom may be, for example, at least one of Cl, S, P, N, etc. When not substituted by heteroatoms, it is a better choice, because the introduction of heteroatoms, on the one hand, makes the reaction complicated and difficult to control, and on the other hand, it may also cause heteroatoms to enter the graphene lattice formed in the liquid phase reaction, thereby introducing more defects, destroying the periodic structure of carbon atoms in the graphene microsheets, causing the final product to have a decreased conductivity, and in the subsequent lithium ion battery charge and discharge test process, uncontrollable side reactions occur at the graphene impurity atom sites, resulting in an increase in the internal resistance of the battery, thereby affecting the battery cycle performance.

[0025] The present invention has no particular limitation on the type of sulfonating agent, which may be any existing substance capable of replacing some hydrogen atoms in an organic material with sulfonic acid groups to achieve sulfonation, such as at least one of chlorosulfonic acid, concentrated sulfuric acid, fuming sulfuric acid, etc., preferably chlorosulfonic acid.

[0026] In the present invention, in step S1, the temperature of the pre-reaction is 30-35°C, such as 30°C, 31°C, 32°C, 33°C, 34°C, 35°C or any value therebetween. When the pre-reaction temperature is lower than 30°C, the organic material cannot be effectively dehydrogenated to form a free monomer, which will affect the subsequent nucleation and the synthesis of graphene in the liquid phase; when the pre-reaction temperature is higher than 35°C, the organic material dehydrogenates and polycondenses, the nucleation growth rate is accelerated, and it will quickly fuse into a large-diameter carbon film, and the sulfonated graphene formed will form a pomegranate shape when the positive electrode material is subsequently wrapped, and the positive electrode material particles cannot be effectively wrapped therein, so that the effective improvement of the conductivity of the positive electrode material cannot be achieved, which will affect the capacity of the lithium-ion battery. The pre-reaction time can be reasonably selected according to the reaction temperature, as long as the organic material can be dehydrogenated, condensed and carbonized with the sulfonating agent as a catalyst and preliminarily decomposed into a disordered carbon film at the nanometer scale. Specifically, the pre-reaction time is preferably 15 minutes to 40 minutes, such as 15 minutes, 18 minutes, 20 minutes, 22 minutes, 25 minutes, 28 minutes, 30 minutes, 32 minutes, 35 minutes, 38 minutes, 40 minutes or any value therebetween. The temperature and time of the pre-reaction can be any point value within the above range, which is not enumerated here.

[0027] In the present invention, in order to make the pre-reaction more sufficient, preferably, the pre-reaction is carried out under stirring. The stirring rate is preferably 150 to 350 rpm, such as 150 rpm, 180 rpm, 200 rpm, 220 rpm, 250 rpm, 280 rpm, 300 rpm, 320 rpm, 350 rpm or any value therebetween. The stirring rate can be any point value within the above range, which is not enumerated here.

[0028] In the present invention, the pre-reaction product needs to be dispersed in water before a high-pressure hydrothermal reaction is carried out. The purpose of dispersing the pre-reaction product in water first is to terminate the further fusion growth reaction of small-diameter carbon microsheets formed at a lower temperature. Among them, the mass ratio of the pre-reaction product to water is preferably 1: (1 to 5), specifically 1: 1, 1: 1.5, 1: 2, 1: 2.5, 1: 3, 1: 3.5, 1: 4, 1: 4.5, 1: 5 or any value therebetween. The ratio between the pre-reaction product and water can be any point value within the above range, which is not enumerated here.

[0029] In the present invention, the pre-reaction product can be dispersed in water by adding the pre-reaction product to water at one time and stirring and dispersing it uniformly, or by adding the pre-reaction product to water in batches and stirring and dispersing it uniformly. It is particularly preferred that the pre-reaction product is slowly added to the water, and continued to be stirred for 5 to 30 minutes (such as 5 minutes, 8 minutes, 10 minutes, 12 minutes, 15 minutes, 18 minutes, 20 minutes, 22 minutes, 25 minutes, 28 minutes, 30 minutes or any value therebetween) after the addition is completed. The above preferred method is adopted to achieve dispersion, which can avoid the agglomeration of the pre-reaction product in water, and make the pre-reaction product in a state of curling, winding, etc. On the contrary, the pre-reaction product can be fully stretched in water, so that the structure repair in the high-pressure hydrothermal reaction is transformed from a disordered structure to an ordered structure, and the final product nanoscale carbon material microsheet morphology still maintains a stretched state, which is conducive to good coating of the positive electrode material, and the carbon material is fully utilized, giving the positive electrode material better conductivity and structural stability, thereby being more conducive to improving the rate performance and cycle performance of the lithium ion battery. In addition, the rate at which the pre-reaction product is added dropwise to water is preferably 2 to 20 mL / min, such as 2, 4, 6, 8, 10, 12, 14, 16, 18, 20 mL / min or any value therebetween.

[0030] In the present invention, the temperature of the high-pressure hydrothermal reaction needs to be controlled at 160-220°C, specifically 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C or any value therebetween. When the high-pressure hydrothermal reaction temperature is lower than 160°C, the pre-reaction product carbon microsheet cannot be effectively transformed from an amorphous carbon structure to a carbon structure with a higher degree of crystallinity, and the sulfonic acid radical obtained by the dissociation of sulfuric acid cannot be firmly suspended on the surface or edge of the carbon material, and thus nano-scale sulfonated graphene with good water solubility cannot be formed. When the high-pressure hydrothermal reaction temperature is higher than 220°C, the dissociation and transformation of sulfuric acid molecules in the solution into sulfonate groups is hindered, and they will dissociate into other products, resulting in a low concentration of sulfonate groups, so they cannot be effectively grafted with graphene microsheets. Moreover, when it is higher than 220°C, the sulfonate groups suspended on the graphene microsheets will also fall off, resulting in poor water solubility of the final product, and it is impossible to "wettably wrap" the surface of the substrate like a similar liquid solution, so it is not conducive to the uniform coating of the positive electrode material in the liquid phase. The pressure of the high-pressure hydrothermal reaction is preferably 1.5 to 2.5 MPa, specifically 1.5 MPa, 1.8 MPa, 2 MPa, 2.2 MPa, 2.5 MPa or any value therebetween. The time of the high-pressure hydrothermal reaction is preferably 4 to 8 hours, specifically 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours or any value therebetween. The temperature, pressure and time of the high-pressure hydrothermal reaction can be any point value within the above range, which are not enumerated here.

[0031] In the present invention, in step S2, the heating rate of heating the dispersion formed by the pre-reaction product and water to the high-pressure hydrothermal reaction temperature is preferably 10-15°C / min, specifically 10, 11, 12, 13, 14, 15°C / min or any value therebetween, at which time, the lithium-ion battery can be given better rate performance and cycle performance. It is speculated that the reason may be that: when the temperature is raised at this heating rate, the organic material that is not completely dehydrogenated in the pre-reaction product is conducive to its full reaction and conversion into carbon material microsheets, and it can ensure that the nano-scale carbon material microsheet morphology always remains in a stretched state, and at the same time, it can ensure that the sulfuric acid in the solution gradually dissociates to form sulfonic acid groups, and then selectively grafts on the surface and edge of the graphene microsheets to avoid affecting the water solubility or conductivity of the final product, so that after it is coated on the positive electrode material, it can show better electrochemical performance when used in lithium-ion batteries in the future.

[0032] In a preferred embodiment, the preparation method of sulfonated graphene further comprises dispersing the obtained product after the high-pressure hydrothermal reaction, then centrifuging the obtained dispersed product to remove slag, then dialyzing and cleaning the upper solution, and spray drying the obtained retentate to obtain sulfonated graphene powder. The dispersion treatment can be specifically ultrasonic dispersion, mechanical stirring dispersion, and ultrasonic dispersion and mechanical stirring dispersion can be performed simultaneously. The time of the dispersion treatment is preferably 1 to 3 hours, and can specifically be 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours or any value therebetween. In addition, the centrifugal speed is preferably 6000-8000 rpm, specifically 6000, 6200, 6400, 6600, 6800, 7000, 7200, 7400, 7600, 7800, 8000 rpm; the centrifugal treatment time is preferably 5-10 min, specifically 5 min, 5.5 min, 6 min, 6.5 min, 7 min, 7.5 min, 8 min, 8.5 min, 9 min, 9.5 min, 10 min or any value therebetween. Centrifugal deslagging is to remove the organic material precursors that have not been completely reacted and the carbon material micro-sheets that have not been formed into water-soluble micro-sheets in the form of precipitation. In addition, the particle size D50 of the sulfonated graphene powder is 20nm to 30nm, such as 20nm, 20.5nm, 21nm, 21.5nm, 22nm, 22.5nm, 23nm, 23.5nm, 24nm, 24.5nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm or any value therebetween; and the particle size D99 is 100nm to 110nm, such as 100nm, 102nm, 104nm, 106nm, 108nm, 110nm or any value therebetween.

[0033] The invention also provides sulfonated graphene prepared by the method.

[0034] The present invention also provides the use of the sulfonated graphene as a carbon material coating agent for positive electrode materials.

[0035] The present invention also provides a modified positive electrode material, wherein the modified positive electrode material comprises a positive electrode material substrate and a coating layer coated on the surface of the positive electrode material substrate, and the coating layer is formed by the above-mentioned sulfonated graphene. The improvement of the modified positive electrode material provided by the present invention is that a new coating layer material is adopted, and the type of positive electrode material and the ratio between the positive electrode material and the coating layer can be conventionally selected in the art, which is known to those skilled in the art and will not be elaborated here.

[0036] The preparation method of the modified positive electrode material provided by the present invention comprises dispersing the above-mentioned sulfonated graphene in water, then uniformly mixing the obtained sulfonated graphene dispersion with the positive electrode material and / or the positive electrode material precursor, and then filtering, drying and calcining the obtained mixture in sequence to obtain the modified positive electrode material.

[0037] In the preparation process of the modified positive electrode material, the usage ratio of the sulfonated graphene to water is preferably (100-140) g:1L, such as 100 g:1L, 110 g:1L, 120 g:1L, 130 g:1L, 140 g:1L or any value therebetween.

[0038] In the preparation process of the modified positive electrode material, the mass ratio of the sulfonated graphene to the positive electrode material and / or the positive electrode material precursor is preferably (1-2):100, such as 1.0:100, 1.2:100, 1.4:100, 1.6:100, 1.8:100, 2.0:100 or any value therebetween.

[0039] In the preparation process of the above-mentioned modified positive electrode material, the drying conditions preferably include a temperature of 80-120°C, such as 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C or any value therebetween; and a time of 5-8h, such as 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h or any value therebetween.

[0040] In the preparation process of the above-mentioned modified positive electrode material, the calcination conditions preferably include a temperature of 600-650°C, such as 600°C, 605°C, 610°C, 615°C, 620°C, 625°C, 630°C, 635°C, 640°C, 645°C, 650°C or any value therebetween; and a time of 6-8h, such as 6h, 6.2h, 6.5h, 6.8h, 7h, 7.2h, 7.4h, 7.6h, 7.8h, 8h or any value therebetween.

[0041] The present invention will be described in detail below through examples.

[0042] Preparation Example 1

[0043] S1. A three-necked flask was fixed in a water bath, and 1000 mL of chlorosulfonic acid and polypropylene (purchased from Suzhou Qihuida Engineering Plastics Co., Ltd., brand T30S, number average molecular weight of 20000) were added to the three-necked flask in sequence, the mass ratio of polypropylene to chlorosulfonic acid was 1:10, and the water bath was heated to 30°C and stirred at 200 rpm by mechanical stirring for 40 minutes to obtain a pre-reaction product;

[0044] S2. The pre-reaction product was slowly added to pure water and stirred at 200 rpm. The mass ratio of the pre-reaction product to pure water was 1:1. The dropping speed was controlled at 2 mL / min. After the dropping was completed, stirring was continued for 15 min to obtain a dispersion. The dispersion was transferred to a polytetrafluoroethylene liner reactor, heated to 160 ° C at a rate of 10 ° C / min, and reacted at 160 ° C and 1.5 MPa for 8 h. The obtained reaction product was ultrasonically dispersed (power was 60 KHz) and equipped with mechanical stirring (stirring rate was 200 rpm) for 2 h, and then the dispersed product was centrifuged at a speed of 6000 rpm for 10 min. The upper filtrate after centrifugation was dialyzed until the pH value was close to neutral. The obtained retentate was spray dried. The inlet temperature of the spray drying was controlled at 220 ° C and the feed rate was controlled at 0.7 L / h to obtain sulfonated graphene powder, which was recorded as HM-1.

[0045] The mass of the precipitated residue after centrifugation of the dispersed product after washing and drying is recorded as m1, and the mass of the precursor polypropylene is recorded as m2. According to the conversion rate of the precursor polypropylene (m2-m1) / m2*100%, the conversion rate of the precursor in this embodiment is calculated to be 98.1%, indicating that the method provided in this embodiment can make the catalytic dehydrogenation condensation of the precursor organic material polypropylene and the nucleation-growth of graphene more sufficient, and basically convert them into sulfonated graphene with good water solubility.

[0046] The laser particle size analyzer test shows that the particle size D50 of the sulfonated graphene powder is 20nm and D99 is 100nm. The Raman spectrum results of the sulfonated graphene powder are shown in Figure 1 , Figure 1 The characteristic signal of graphene 2D peak can be clearly seen. Although there are certain defects as seen from the Raman spectrum, compared with the disordered structure of activated carbon, the lattice structure of the sulfonated graphene prepared in this example is significantly repaired.

[0047] The SEM image of the sulfonated graphene powder is as follows Figure 2 As shown, from Figure 2 It can be seen that a large number of regular spheres are formed after spray drying. According to the general characteristics of nanomaterials, the droplets formed by spraying a mixed solution of small-sized nanoparticles will form spherical particles after rapid drying. In addition, since nanoscale microsheets are difficult to observe under an electron microscope, this method can indirectly explain that the size of the sulfonated graphene powder obtained by the method of this embodiment is small.

[0048] EDS elemental analysis shows that C:S = 7.72:1. The infrared spectrum of the sulfonated graphene powder is shown in Figure 3 As shown, from Figure 3 It can be seen that at wave number 1178cm -1 、1060cm -1There are characteristic peaks near the -SO3H group, which indicates that the sulfonic acid group has been successfully bonded to the graphene. The resistivity of the sulfonated graphene powder prepared in this embodiment is 33 mΩ.cm when tested by a powder resistivity tester, indicating that the sulfonated graphene prepared in this embodiment has good conductive properties.

[0049] Preparation Example 2

[0050] S1. A three-necked flask was fixed in a water bath, and 1000 mL of chlorosulfonic acid and polypropylene (purchased from Suzhou Qihuida Engineering Plastics Co., Ltd., brand T20, number average molecular weight of 15000) were added to the three-necked flask in sequence, the mass ratio of polypropylene to chlorosulfonic acid was 1:15, and the water bath was heated to 35°C and stirred at 350 rpm for 15 min by mechanical stirring to obtain a pre-reaction product;

[0051] S2. The pre-reaction product was slowly added to pure water and stirred at 200 rpm. The mass ratio of the pre-reaction product to pure water was 1:1.5. The dropping speed was controlled at 5 mL / min. After the dropping was completed, stirring was continued for 25 min to obtain a dispersion. The dispersion was transferred to a polytetrafluoroethylene liner reactor, heated to 220 ° C at a rate of 15 ° C / min, and reacted at a temperature of 220 ° C and a pressure of 2.5 MPa for 4 h. The obtained reaction product was ultrasonically dispersed (power of 40 KHz) and equipped with mechanical stirring (stirring rate of 200 rpm) for 3 h, and then the dispersed product was centrifuged at a speed of 7000 rpm for 8 min and filtered. The upper filtrate after centrifugation was dialyzed until the pH value was close to neutral. The obtained retentate was spray dried, the inlet temperature of the spray drying was controlled at 200 ° C, and the feed rate was controlled at 0.5 L / h to obtain sulfonated graphene powder, recorded as HM-2.

[0052] The mass of the precipitated residue after centrifugation of the dispersed product after washing and drying is recorded as m1, and the mass of the precursor polypropylene is recorded as m2. According to the conversion rate of the precursor polypropylene (m2-m1) / m2*100%, the conversion rate of the precursor in this embodiment is calculated to be 98.5%, indicating that the method provided in this embodiment can make the catalytic dehydrogenation condensation of the precursor organic material polypropylene and the nucleation-growth of graphene more sufficient, and basically convert them into sulfonated graphene with good water solubility.

[0053] It can be seen from the SEM image that the sulfonated graphene powder obtained after spray drying is spherical. According to the general characteristics of nanomaterials, the droplets formed by spraying a mixed solution of small-sized nanoparticles will form spherical particles after rapid drying. In addition, since nanoscale microsheets are difficult to observe under an electron microscope, this method can indirectly explain that the size of the sulfonated graphene powder obtained by the method of this embodiment is small.

[0054] The laser particle size analyzer test shows that the particle size D50 of the sulfonated graphene powder is 22.5nm and D99 is 103.1nm. The Raman spectrum test shows that the 2D characteristic signal of graphene can be clearly seen. Although there are many defects in the Raman spectrum, the lattice structure of the sulfonated graphene prepared in this embodiment is significantly repaired compared with the disordered structure of activated carbon. EDS elemental analysis shows that C:S = 7.81:1; infrared spectrum test shows that at the wave number 1178cm -1 、1060cm -1 There are characteristic peaks near the -SO3H group, which indicates that the sulfonic acid group has been successfully bonded to the graphene. The resistivity of the sulfonated graphene powder prepared in this embodiment is 34.5 mΩ.cm when tested by a powder resistivity tester, indicating that the sulfonated graphene prepared in this embodiment has good conductive properties.

[0055] Preparation Example 3

[0056] S1. A three-necked flask was fixed in a water bath, and 1000 mL of chlorosulfonic acid and polypropylene (purchased from Nanjing Tianshi New Material Technology Co., Ltd., brand PPW-0910, number average molecular weight of 40000) were added to the three-necked flask in sequence, the mass ratio of polypropylene to chlorosulfonic acid was 1:20, and the water bath was heated to 32 ° C and stirred at 150 rpm by mechanical stirring for 25 min to obtain a pre-reaction product;

[0057] S2. The pre-reaction product was slowly added to pure water and stirred at 200 rpm. The mass ratio of the pre-reaction product to pure water was 1:5. The dropping speed was controlled at 20 mL / min. After the dropping was completed, stirring was continued for 20 min to obtain a dispersion. The dispersion was transferred to a polytetrafluoroethylene liner reactor, heated to 200 ° C at a rate of 13 ° C / min, and reacted at a temperature of 200 ° C and a pressure of 2.35 MPa for 6 h. The obtained reaction product was ultrasonically dispersed (power of 80 KHz) and equipped with mechanical stirring (stirring rate of 200 rpm) for 1 h, and then the dispersed product was centrifuged at a speed of 8000 rpm for 5 min. The upper filtrate after centrifugation was dialyzed until the pH value was close to neutral. The obtained retentate was spray dried, the inlet temperature of the spray drying was controlled at 210 ° C, and the feed rate was controlled at 0.6 L / h to obtain sulfonated graphene powder, recorded as HM-3.

[0058] The mass of the precipitated residue after centrifugation of the dispersed product after washing and drying is recorded as m1, and the mass of the precursor polypropylene is recorded as m2. According to the conversion rate of the precursor polypropylene (m2-m1) / m2*100%, the precursor conversion rate of this embodiment is calculated to be 97.8%, indicating that the method provided in this embodiment can make the catalytic dehydrogenation condensation of the precursor organic material polypropylene and the nucleation-growth of graphene more sufficient, and basically convert them into sulfonated graphene with good water solubility.

[0059] It can be seen from the SEM image that the sulfonated graphene powder obtained after spray drying is spherical. According to the general characteristics of nanomaterials, the droplets formed by spraying a mixed solution of small-sized nanoparticles will form spherical particles after rapid drying. In addition, since nanoscale microsheets are difficult to observe under an electron microscope, this method can indirectly explain that the size of the sulfonated graphene powder obtained by the method of this embodiment is small.

[0060] The laser particle size analyzer test shows that the particle size D50 of the sulfonated graphene powder is 20.5nm and D99 is 102.3nm. The Raman spectrum test shows that the 2D characteristic signal of graphene can be clearly seen. Although there are certain defects in the Raman spectrum, the lattice structure of the sulfonated graphene prepared in this embodiment is significantly repaired compared to the disordered structure of activated carbon. EDS elemental analysis shows that C:S = 7.79:1; infrared spectrum test shows that at the wave number 1178cm -1 、1060cm -1 There are characteristic peaks near the -SO3H group, which indicates that the sulfonic acid group has been successfully bonded to the graphene. The resistivity of the sulfonated graphene powder prepared in this embodiment is 34.1 mΩ.cm when tested by a powder resistivity tester, indicating that the sulfonated graphene prepared in this embodiment has good conductive properties.

[0061] Preparation Example 4

[0062] Sulfonated graphene was prepared according to the method of Preparation Example 1, except that polypropylene was replaced by polyethylene of the same weight and equivalent molecular weight (purchased from Nanjing Tianshi New Material Technology Co., Ltd., brand PEW-0320, number average molecular weight of 20000), and the other conditions were the same as those in Preparation Example 1 to obtain sulfonated graphene powder, which was recorded as HM-4.

[0063] The mass of the precipitated residue after centrifugation of the dispersed product after washing and drying is recorded as m1, and the mass of the precursor polyethylene is recorded as m2. The precursor conversion rate of this embodiment is calculated according to the precursor polyethylene conversion rate (m2-m1) / m2*100%, and the precursor conversion rate is 98.3%. It means that the method provided in this embodiment can make the catalytic dehydrogenation and condensation of the precursor organic material polyethylene and the nucleation and growth of graphene more sufficient, and basically convert them into sulfonated graphene with good water solubility.

[0064] It can be seen from the SEM image that the sulfonated graphene powder obtained after spray drying is spherical. According to the general characteristics of nanomaterials, the droplets formed by spraying a mixed solution of small-sized nanoparticles will form spherical particles after rapid drying. In addition, since nanoscale microsheets are difficult to observe under an electron microscope, this method can indirectly explain that the size of the sulfonated graphene powder obtained by the method of this embodiment is small.

[0065] The laser particle size analyzer test shows that the particle size D50 of the sulfonated graphene powder is 22.7nm and D99 is 103.4nm. The Raman spectrum test shows that the characteristic signal of the graphene 2D peak can be clearly seen. Although there are certain defects from the Raman spectrum, the lattice structure of the sulfonated graphene prepared in this embodiment is significantly repaired compared to the disordered structure of activated carbon. EDS elemental analysis shows that C:S = 7.78:1; in addition, the infrared spectrum test shows that at the wave number 1178cm -1 、1060cm -1 There are characteristic peaks near the -SO3H group, which indicates that the sulfonic acid group has been successfully bonded to the graphene. The resistivity of the sulfonated graphene powder prepared in this embodiment is 34.3 mΩ.cm when tested by a powder resistivity tester, indicating that the sulfonated graphene prepared in this embodiment has good conductive properties.

[0066] Preparation Example 5

[0067] Sulfonated graphene was prepared according to the method of Preparation Example 1, except that polypropylene was replaced with polystyrene (purchased from BASF-YPC Co., Ltd., brand 143E, number average molecular weight 35000) of the same weight and molecular weight, and the other conditions were the same as those in Preparation Example 1 to obtain sulfonated graphene powder, which was recorded as HM-5.

[0068] The mass of the precipitated residue after centrifugation of the dispersed product after washing and drying is recorded as m1, and the mass of the precursor polystyrene is recorded as m2. According to the conversion rate of the precursor polystyrene (m2-m1) / m2*100%, the precursor conversion rate of this embodiment is calculated to be 98.1%, indicating that the method provided in this embodiment can make the catalytic dehydrogenation and condensation of the precursor organic material polystyrene and the nucleation and growth of graphene more sufficient, and basically convert them into sulfonated graphene with good water solubility.

[0069] It can be seen from the SEM image that the sulfonated graphene powder obtained after spray drying is spherical. According to the general characteristics of nanomaterials, the droplets formed by spraying a mixed solution of small-sized nanoparticles will form spherical particles after rapid drying. In addition, since nanoscale microsheets are difficult to observe under an electron microscope, this method can indirectly explain that the size of the sulfonated graphene powder obtained by the method of this embodiment is small.

[0070] According to the laser particle size analyzer test, the particle size D50 of the sulfonated graphene powder is 20.3nm, and D99 is 101.2nm. According to the Raman spectrum test, the 2D characteristic signal of graphene can be clearly seen. Although there are certain defects from the Raman spectrum, the lattice structure of the sulfonated graphene prepared in this embodiment is significantly repaired compared with the disordered structure of activated carbon. According to the EDS elemental analysis calculation, C:S=7.75:1; in addition, according to the infrared spectrum test, at the wave number 1178cm -1 、1060cm -1 There are characteristic peaks near the -SO3H group, which indicates that the sulfonic acid group has been successfully bonded to the graphene. The resistivity of the sulfonated graphene powder prepared in this embodiment is 33.6 mΩ.cm when tested by a powder resistivity tester, indicating that the sulfonated graphene prepared in this embodiment has good conductive properties.

[0071] Preparation Example 6

[0072] Sulfonated graphene was prepared according to the method of Preparation Example 1, except that in step S2, the pre-reaction product was added to water at one time, and the other conditions were the same as those of Preparation Example 1. The specific steps were as follows:

[0073] S1. A three-necked flask was fixed in a water bath, and 1000 mL of chlorosulfonic acid and polypropylene (purchased from Suzhou Qihuida Engineering Plastics Co., Ltd., brand T30S, number average molecular weight of 20000) were added to the three-necked flask in sequence, the mass ratio of polypropylene to chlorosulfonic acid was 1:10, and the water bath was heated to 30°C and stirred at 200 rpm by mechanical stirring for 40 minutes to obtain a pre-reaction product;

[0074] S2. The pre-reaction product was added to pure water at a stirring state of 200 rpm at one time, and the mass ratio of the pre-reaction product to pure water was 1:1. After the addition was completed, the mixture was stirred at 200 rpm for 15 min to obtain a dispersion. The dispersion was transferred to a polytetrafluoroethylene liner reactor, heated to 160°C at a rate of 10°C / min, and reacted at 160°C and 1.5 MPa for 8 h. The obtained reaction product was dispersed by ultrasound (power of 60 KHz) and mechanical stirring (stirring rate of 200 rpm) for 2 h, and then the dispersed product was centrifuged at a speed of 6000 rpm for 10 min. The upper filtrate after centrifugation was dialyzed until the pH value was close to neutral. The obtained retentate was spray dried, and the inlet temperature of the spray drying was controlled at 220°C and the feed rate was controlled at 0.7 L / h to obtain sulfonated graphene powder, which was recorded as HM-6.

[0075] The mass of the precipitated residue after centrifugation of the dispersed product after washing and drying is recorded as m1, and the mass of the precursor polypropylene is recorded as m2. According to the conversion rate of the precursor polypropylene (m2-m1) / m2*100%, the precursor conversion rate of this embodiment is calculated to be 97.7%, indicating that the method provided in this embodiment can make the catalytic dehydrogenation condensation of the precursor organic material polypropylene and the nucleation-growth of graphene more sufficient, and basically convert them into sulfonated graphene with good water solubility.

[0076] It can be seen from the SEM image that the sulfonated graphene powder obtained after spray drying is spherical. According to the general characteristics of nanomaterials, the droplets formed by spraying a mixed solution of small-sized nanoparticles will form spherical particles after rapid drying. In addition, since nanoscale microsheets are difficult to observe under an electron microscope, this method can indirectly explain that the size of the sulfonated graphene powder obtained by the method of this embodiment is small.

[0077] The particle size D50 of the sulfonated graphene powder was 21.4nm and D99 was 103.1nm as tested by a laser particle size analyzer. The 2D characteristic signal of graphene can be clearly seen by Raman spectroscopy. Although there are certain defects in the Raman spectrum, the lattice structure of the sulfonated graphene prepared in this embodiment is significantly repaired compared to the disordered structure of activated carbon. EDS elemental analysis shows that C:S = 7.85:1. Infrared spectroscopy shows that at the wave number 1178cm -1 、1060cm -1 There are characteristic peaks near the -SO3H group, which indicates that the sulfonic acid group has been successfully bonded to the graphene. The resistivity of the sulfonated graphene powder prepared in this embodiment is 33.8 mΩ.cm when tested by a powder resistivity tester, indicating that the sulfonated graphene prepared in this embodiment has good conductive properties.

[0078] Preparation Example 7

[0079] Sulfonated graphene was prepared according to the method of Preparation Example 1, except that the heating rate of the dispersion formed by the pre-reaction product and water to the high-pressure hydrothermal reaction temperature was controlled at 7°C / min (i.e., not within the preferred range of the present invention), and the other conditions were the same as those in Preparation Example 1 to obtain sulfonated graphene powder, which was recorded as HM-7.

[0080] The mass of the precipitated residue after centrifugation of the dispersed product after washing and drying is recorded as m1, and the mass of the precursor polypropylene is recorded as m2. According to the conversion rate of the precursor polypropylene (m2-m1) / m2*100%, the precursor conversion rate of this embodiment is calculated to be 97.6%, indicating that the method provided in this embodiment can make the catalytic dehydrogenation condensation of the precursor organic material polypropylene and the nucleation-growth of graphene more sufficient, and basically convert them into sulfonated graphene with good water solubility.

[0081] It can be seen from the SEM image that the sulfonated graphene powder obtained after spray drying is spherical. According to the general characteristics of nanomaterials, the droplets formed by spraying a mixed solution of small-sized nanoparticles will form spherical particles after rapid drying. In addition, since nanoscale microsheets are difficult to observe under an electron microscope, this method can indirectly explain that the size of the sulfonated graphene powder obtained by the method of this embodiment is small.

[0082] The laser particle size analyzer test shows that the particle size D50 of the sulfonated graphene powder is 20.7nm and D99 is 101.5nm. The Raman spectrum test shows that the 2D characteristic signal of graphene can be clearly seen. Although there are certain defects in the Raman spectrum, the lattice structure of the sulfonated graphene prepared in this embodiment is significantly repaired compared to the disordered structure of activated carbon. EDS elemental analysis shows that C:S = 7.8:1. The infrared spectrum test shows that at the wave number 1178cm -1 、1060cm -1 There are characteristic peaks near the -SO3H group, which indicates that the sulfonic acid group has been successfully bonded to the graphene. The resistivity of the sulfonated graphene powder prepared in this embodiment is 34.0 mΩ.cm when tested by a powder resistivity tester, indicating that the sulfonated graphene prepared in this embodiment has good conductive properties.

[0083] Comparative Preparation Example 1

[0084] Sulfonated graphene was prepared according to the method of Preparation Example 1, except that the pre-reaction temperature of step S1 was controlled at 40° C. The other conditions were the same as those of Preparation Example 1, and sulfonated graphene powder was obtained, which was recorded as DHM-1.

[0085] The mass of the precipitated residue after centrifugation of the dispersed product after washing and drying is recorded as m1, and the mass of the precursor polypropylene is recorded as m2. According to the conversion rate of the precursor polypropylene (m2-m1) / m2*100%, the precursor conversion rate of this embodiment is calculated to be 98.3%, indicating that the method provided in this embodiment can make the catalytic dehydrogenation condensation of the precursor organic material polypropylene and the nucleation-growth of graphene more sufficient, and basically convert them into sulfonated graphene with good water solubility.

[0086] According to the test of laser particle size analyzer, the particle size D50 of the sulfonated graphene powder is 30μm, and D99 is 75μm. The flake diameter is relatively large. It may be due to the high pre-reaction temperature and the fast nucleation growth rate. The carbon microflakes formed by the dehydrogenation and polycondensation of the precursor quickly merge into a large-diameter carbon film. According to the Raman spectrum test, the 2D characteristic signal of graphene can be clearly seen. Although there are certain defects from the Raman spectrum, the lattice structure of the sulfonated graphene prepared in this embodiment is significantly repaired compared with the disordered structure of activated carbon. It can be seen from the EDS elemental analysis calculation that C:S=7.96:1. According to the infrared spectrum test, at the wave number 1178cm -1 、1060cm -1 There are characteristic peaks near the -SO3H group, which indicates that the sulfonic acid group has been successfully bonded to the graphene. The resistivity of the sulfonated graphene powder prepared in this embodiment is 34.7 mΩ.cm when tested by a powder resistivity tester, indicating that the sulfonated graphene prepared in this embodiment has good conductive properties.

[0087] Comparative Preparation Example 2

[0088] Sulfonated graphene was prepared according to the method of Preparation Example 1, except that the pre-reaction in step S1 was carried out in water, and no water was added in step S2. The specific steps were as follows:

[0089] S1. Fix a three-necked flask in a water bath, add 1000 mL of chlorosulfonic acid, polypropylene and water to the three-necked flask in sequence, the mass ratio of polypropylene to chlorosulfonic acid is 1:10, the mass ratio of the total amount of polypropylene and chlorosulfonic acid to pure water is 1:1, heat the water bath to 30°C and stir the reaction at 200 rpm for 40 minutes by mechanical stirring to obtain a pre-reaction product;

[0090] S2. The pre-reaction product was transferred to a polytetrafluoroethylene liner reactor, heated to 160°C at a rate of 10°C / min, and reacted at 160°C and 1.5MPa for 8h. The obtained reaction product was dispersed by ultrasound (power of 60KHz) and mechanical stirring (stirring rate of 200rpm) for 2h, and then the dispersed product was centrifuged at 6000 rpm for 10min. The upper filtrate after centrifugation was dialyzed until the pH value was close to neutral. The obtained retentate was spray-dried, the inlet temperature of the spray drying was controlled at 220°C, and the feed rate was controlled at 0.7L / h to obtain the target product, recorded as DHM-2.

[0091] The mass of the precipitated residue after centrifugation of the dispersed product after washing and drying is recorded as m1, and the mass of the precursor polypropylene is recorded as m2. According to the conversion rate of the precursor polypropylene (m2-m1) / m2*100%, the precursor conversion rate of this embodiment is calculated to be 15%, indicating that the method provided in this embodiment inhibits the dehydrogenation polycondensation of the precursor polypropylene and the nucleation growth of graphene in the liquid phase, thereby affecting the synthesis of nanoscale graphene microsheets, resulting in a significant decrease in the precursor conversion rate. According to the laser particle size analyzer test, the particle size D50 of the sulfonated graphene powder is 23nm, and D99 is 104nm. Raman spectroscopy test, such as Figure 4 As shown in the figure, the 2D characteristic signal of graphene can be seen, but the defects are obviously increased. This may be because the pre-reaction stage is carried out in water medium, which not only reacts slowly but also randomly condenses and carbonizes, resulting in poor nucleation and many defects in the final product. EDS elemental analysis shows that C:S = 8.05:1. According to infrared spectroscopy test, at the wave number 1178cm -1 、1060cm -1 There are characteristic peaks near the -SO3H group, which indicates that the sulfonic acid group has been successfully bonded to the graphene. The resistivity of the sulfonated graphene powder prepared in this embodiment is 55.4 mΩ.cm when tested by a powder resistivity tester. The conductivity of the powder is poor, which may be related to the increase in defects.

[0092] Comparative Preparation Example 3

[0093] Sulfonated graphene was prepared according to the method of Preparation Example 1, except that the water in step S2 was replaced by the same weight of hexadecane. The other conditions were the same as those of Preparation Example 1, and sulfonated graphene powder was obtained, which was recorded as DHM-3.

[0094] Tested by a laser particle size analyzer, the particle size D50 of the sulfonated graphene powder is 37μm, and D99 is 82μm, and the flake diameter has increased significantly. This may be because hexadecane provides a carbon source to participate in the reaction in the high-pressure hydrothermal reaction, so that the carbon microflakes formed in the pre-reaction are further enlarged while their structure is repaired in the high-pressure hydrothermal reaction.

[0095] The mass of the precipitated residue after centrifugation of the dispersed product after washing and drying is recorded as m1, and the mass of the precursor polypropylene is recorded as m2. The precursor conversion rate of this embodiment is calculated according to the conversion rate of the precursor polypropylene (m2-m1) / m2*100%, which is 101.8%, further illustrating that the method provided in this embodiment uses hexadecane to provide a carbon source to participate in the reaction.

[0096] The Raman spectrum test shows that the characteristic signal of graphene can be clearly seen. Although there are certain defects in the Raman spectrum, the lattice structure of the sulfonated graphene prepared in this embodiment is significantly repaired compared with the disordered structure of activated carbon. EDS elemental analysis shows that C:S = 7.98:1. The infrared spectrum test shows that at the wave number 1178cm -1 、1060cm -1 There are characteristic peaks near the -SO3H group, which indicates that the sulfonic acid group has been successfully bonded to the graphene. The resistivity of the sulfonated graphene powder prepared in this embodiment is 34.0 mΩ.cm when tested by a powder resistivity tester, indicating that the sulfonated graphene prepared in this embodiment has good conductive properties.

[0097] Comparative Preparation Example 4

[0098] In a fume hood, 600 g of 99% pure chlorosulfonic acid was added as a reaction medium to an open 2L three-necked glass reactor. The reactor was heated to 50°C using an oil bath and maintained at this temperature. 10 g of hexadecane was added and reacted for 3 h. The temperature was then slowly raised to 160°C and kept at this temperature for 12 h. The reaction was cooled and the contents of the reactor were centrifuged at 6000 rpm for 10 min. The upper filtrate after centrifugation was dialyzed and dried to obtain sulfonated graphene, which was recorded as DHM-4.

[0099] The mass of the precipitated residue after centrifugation of the dispersed product after washing and drying is recorded as m1, and the mass of the precursor hexadecane is recorded as m2. The conversion rate of the precursor hexadecane is calculated according to (m2-m1) / m2*100%, and the precursor conversion rate of this embodiment is 97.1%, indicating that the method provided in this embodiment can make the catalytic dehydrogenation and condensation of the precursor organic material hexadecane and the nucleation and growth of graphene more sufficient, and basically convert them into sulfonated graphene with good water solubility.

[0100] According to the laser particle size analyzer test, the particle size D50 of the sulfonated graphene powder is 47μm, and D99 is 95μm. The flake diameter has increased significantly. This may be due to the violent reaction of hexadecane in the chlorosulfonic acid medium, and the high pre-reaction temperature, which leads to a fast nucleation growth rate, resulting in the formation of larger carbon micro-flakes. After the high-pressure hydrothermal reaction, the final product flake diameter is also significantly larger. According to the Raman spectrum test, the characteristic signal of graphene can be clearly seen. According to the EDS elemental analysis calculation, C:S=7.76:1. According to the infrared spectrum test, at the wave number 1178cm -1 、1060cm -1There are characteristic peaks near the -SO3H group, which indicates that the sulfonic acid group has been successfully bonded to the graphene. The resistivity of the sulfonated graphene powder prepared in this embodiment is 34.5 mΩ.cm when tested by a powder resistivity tester, indicating that the sulfonated graphene prepared in this embodiment has good conductive properties.

[0101] Example 1

[0102] 20 g of the sulfonated graphene powder HM-1 obtained in Preparation Example 1 was dispersed in 200 mL of water, and the obtained sulfonated graphene dispersion was evenly mixed with the lithium iron phosphate positive electrode material. The mass ratio of the sulfonated graphene to the lithium iron phosphate positive electrode material was 1:100. The obtained mixture was then filtered and dried at 80°C for 8 h. The obtained dry product was then calcined at 650°C with nitrogen protection at a flow rate of 5 L / min for 5 h to obtain a modified positive electrode material.

[0103] Example 2

[0104] A modified positive electrode material was prepared according to the method of Example 1, except that the sulfonated graphene powder HM-1 obtained in Preparation Example 1 was replaced by the sulfonated graphene powder HM-2 obtained in Preparation Example 2 in the same weight portion, and the other conditions were the same as in Example 1 to obtain a modified positive electrode material.

[0105] Example 3

[0106] A modified positive electrode material was prepared according to the method of Example 1, except that the sulfonated graphene powder HM-1 obtained in Preparation Example 1 was replaced by the sulfonated graphene powder HM-3 obtained in Preparation Example 3 with the same weight portion, and the other conditions were the same as in Example 1 to obtain a modified positive electrode material.

[0107] Example 4

[0108] A modified positive electrode material was prepared according to the method of Example 1, except that the sulfonated graphene powder HM-1 obtained in Preparation Example 1 was replaced by the sulfonated graphene powder HM-4 obtained in Preparation Example 4 in the same weight portion, and the other conditions were the same as in Example 1 to obtain a modified positive electrode material.

[0109] Example 5

[0110] A modified positive electrode material was prepared according to the method of Example 1, except that the sulfonated graphene powder HM-1 obtained in Preparation Example 1 was replaced by the sulfonated graphene powder HM-5 obtained in Preparation Example 5 in the same weight portion, and the other conditions were the same as in Example 1 to obtain a modified positive electrode material.

[0111] Example 6

[0112] A modified positive electrode material was prepared according to the method of Example 1, except that the sulfonated graphene powder HM-1 obtained in Preparation Example 1 was replaced by the sulfonated graphene powder HM-6 obtained in Preparation Example 6 in the same weight portion, and the other conditions were the same as in Example 1 to obtain a modified positive electrode material.

[0113] Example 7

[0114] A modified positive electrode material was prepared according to the method of Example 1, except that the sulfonated graphene powder HM-1 obtained in Preparation Example 1 was replaced by the sulfonated graphene powder HM-7 obtained in Preparation Example 7 with the same weight portion, and the other conditions were the same as in Example 1 to obtain a modified positive electrode material.

[0115] Comparative Example 1

[0116] A modified positive electrode material was prepared according to the method of Example 1, except that the sulfonated graphene powder HM-1 obtained in Preparation Example 1 was replaced by the sulfonated graphene powder DHM-1 obtained in Comparative Preparation Example 1 with the same weight portion, and the other conditions were the same as in Example 1 to obtain a modified positive electrode material.

[0117] Comparative Example 2

[0118] A modified positive electrode material was prepared according to the method of Example 1, except that the sulfonated graphene powder HM-1 obtained in Preparation Example 1 was replaced by the sulfonated graphene powder DHM-2 obtained in Comparative Preparation Example 2 with the same weight portion, and the other conditions were the same as in Example 1 to obtain a modified positive electrode material.

[0119] Comparative Example 3

[0120] A modified positive electrode material was prepared according to the method of Example 1, except that the sulfonated graphene powder HM-1 obtained in Preparation Example 1 was replaced by the sulfonated graphene powder DHM-3 obtained in Comparative Preparation Example 3 with the same weight portion, and the other conditions were the same as in Example 1 to obtain a modified positive electrode material.

[0121] Comparative Example 4

[0122] A modified positive electrode material was prepared according to the method of Example 1, except that the sulfonated graphene powder HM-1 obtained in Preparation Example 1 was replaced by the sulfonated graphene powder DHM-4 obtained in Comparative Preparation Example 4 with the same weight portion, and the other conditions were the same as in Example 1 to obtain a modified positive electrode material.

[0123] Test Case

[0124] The modified positive electrode materials obtained in the above examples and comparative examples were mixed with conductive carbon black Super P and binder PVDF in a weight ratio of 92:3:5 in NMP and coated on aluminum foil to obtain pole pieces. The pole pieces were dried in a blast oven at 80°C and then placed in a vacuum oven at 120°C to dry overnight. The dried pole pieces were rolled and used as battery positive electrodes (with a compaction density of 2.3 g / cm 3 ), lithium metal as the battery negative electrode, Celgard2400 as the separator, 1M LiPF6-EC-DMC-EMC (that is, the concentration of LiPF6 in EC-DMC-EMC solvent is 1M, where EC is ethylene carbonate, DMC is dimethyl carbonate, EMC is methyl ethyl carbonate, and the volume ratio of EC:DMC:EMC is 1:1:1) as the electrolyte, assembled into 2032 batteries for electrochemical testing.

[0125] (1) Discharge specific capacity: After the above 2032 battery was placed at 25°C for 6 hours, it was charged at a constant current of 0.1C to a cut-off voltage of 3.85V, then charged at a constant voltage to a cut-off current of 0.02C, and then discharged at a constant current of 7C to a cut-off voltage of 2.0V. The discharge specific capacity of the positive electrode material was obtained by dividing the discharge capacity by the mass of the active material (i.e., the modified positive electrode material). The results are shown in Table 1.

[0126] (2) Cycle performance: After the above CR2032 battery was charged and discharged for 100 times at a current density of 7C in the voltage range of 2 to 3.85V at room temperature, the discharge specific capacity was tested again, and the capacity retention rate was calculated based on the discharge specific capacity after 100 cycles / the initial discharge specific capacity. The results are shown in Table 1.

[0127] (3) Battery impedance: The assembled button cell was subjected to electrochemical impedance testing using an electrochemical workstation at a scanning frequency of 0.1 Hz to 1 MHZ and a voltage amplitude within the range of ±10 mV. The results are shown in Table 1.

[0128] Table 1

[0129]

[0130] It can be seen from the results of Examples 1 to 7 that when the sulfonated graphene obtained by the method provided by the present invention is used to coat the positive electrode material, the rate performance and cycle performance of the lithium-ion battery can be significantly improved.

[0131] From the comparison between Example 1 and Example 6, it can be seen that in step S2, when the pre-reaction product is dispersed in water by slowly dropping the pre-reaction product into water and continuing to stir the reaction for a period of time after the dropping is completed, it is more conducive to improving the rate performance and cycle performance of the lithium-ion battery.

[0132] From the comparison between Example 1 and Example 7, it can be seen that when the heating rate of the dispersion formed by the pre-reaction product and water to the high-pressure hydrothermal reaction temperature is controlled within a preferred range, the lithium-ion battery can be endowed with better rate performance and cycle performance.

[0133] From the comparison between Example 1 and Comparative Example 1, it can be seen that when the pre-reaction temperature exceeds the range of the present application, the capacity of the lithium-ion battery will be affected.

[0134] From the comparison between Example 1 and Comparative Example 2, it can be seen that when the addition sequence of water is advanced to the pre-reaction step, the rate performance and cycle performance of the lithium-ion battery will be reduced.

[0135] From the comparison between Example 1 and Comparative Example 3, it can be seen that when the high-pressure hydrothermal reaction is carried out in a non-aqueous solution, the rate performance and cycle performance of the lithium-ion battery are poor.

[0136] From the comparison between Example 1 and Comparative Example 4, it can be seen that when sulfonated graphene is prepared by conventional methods, the rate performance and cycle performance of lithium-ion batteries cannot be effectively improved.

[0137] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A method for preparing sulfonated graphene, characterized in that: The method comprises the following steps: S1. Pre-reacting the organic material and the sulfonating agent at 30 to 35° C. in the absence of a reaction medium to obtain a pre-reaction product; S2. Dispersing the pre-reaction product in water, and then heating the resulting dispersion to 160-220° C. to perform a high-pressure hydrothermal reaction to obtain sulfonated graphene.

2. The method for preparing sulfonated graphene according to claim 1, characterized in that: In step S1, the mass ratio of the organic material to the sulfonating agent is 1:(10-20); Preferably, the organic material is selected from at least one of polyethylene, polypropylene, polyimide and polystyrene; Preferably, the sulfonating agent is selected from at least one of chlorosulfonic acid, concentrated sulfuric acid and fuming sulfuric acid.

3. The method for preparing sulfonated graphene according to claim 1, characterized in that: In step S1, the pre-reaction time is 15 min to 40 min.

4. The method for preparing sulfonated graphene according to claim 1, characterized in that: In step S2, the mass ratio of the pre-reaction product to water is 1:(1-5); Preferably, the pre-reaction product is dispersed in water by slowly dropping the pre-reaction product into the water, and stirring is continued for 5 to 30 minutes after the dropwise addition is completed; Preferably, the rate of adding the pre-reaction product dropwise into water is 2 to 20 mL / min.

5. The method for preparing sulfonated graphene according to claim 1, characterized in that: In step S2, the dispersion is heated to the high pressure hydrothermal reaction temperature at a rate of 10 to 15°C / min; Preferably, the high pressure hydrothermal reaction time is 4 to 8 hours.

6. The method for preparing sulfonated graphene according to claim 1, characterized in that: The method further comprises dispersing the obtained product after the high-pressure hydrothermal reaction, centrifuging the obtained dispersed product to remove residue, dialysis washing the obtained filtrate, and spray drying the obtained retentate to obtain sulfonated graphene powder; Preferably, the dispersion treatment is carried out by ultrasonic dispersion and / or mechanical stirring dispersion; Preferably, the dispersion treatment time is 1 to 3 hours; Preferably, the particle size D50 of the sulfonated graphene powder is 20 nm to 30 nm and the particle size D99 is 100 nm to 110 nm.

7. Sulfonated graphene prepared by the method according to any one of claims 1 to 6.

8. Use of the sulfonated graphene according to claim 7 as a carbon material coating agent for positive electrode materials.

9. A modified positive electrode material, characterized in that: The modified positive electrode material comprises a positive electrode material matrix and a coating layer coated on the surface of the positive electrode material matrix, and the coating layer is formed by the sulfonated graphene according to claim 7.

10. A method for preparing the modified positive electrode material according to claim 9, the method comprising dispersing the sulfonated graphene according to claim 7 in water, uniformly mixing the obtained sulfonated graphene dispersion with the positive electrode material and / or the positive electrode material precursor, and then filtering, drying and calcining the obtained mixture in sequence to obtain the modified positive electrode material.

Citation Information

Patent Citations

  • Method for preparing sulfonated graphene from organic material and the sulfonated graphene

    CN105764839A

  • Methods for preparing sulfonated graphene from organic materials and sulfonated graphene

    CN105764839B

  • Sulfonated graphene-based carbon-coated lithium titanate composite material and preparation and application thereof

    CN109859960A

  • Carbon-sulfur positive electrode material for lithium-sulfur battery and preparation method of carbon-sulfur positive electrode material

    CN110350182A

  • Graphene modified silicon negative electrode material and preparation method and application thereof

    CN114613955A